Snapshots Quiz. Issue 3 (24th October 2021) - Mazzola, F.; Hertig, T.; Pabst, M.
Abstract : A 60-year-old man presented with acute epigastric pain and diarrhoea. His medical history included chronic obstructive pulmonary disease with recent exacerbation for which he was taking glucocorticoid therapy. What is the name of the clinical sign found on CT scan and correlated intraoperatively?